A Hybrid Secure Watermarking Scheme Using Nonnegative Matrix Factorization and FastWalsh-Hadamard Transform. Issue 2 (2nd April 2020) - Abdallah, Emad E.; Otoom, Ahmed Fawzi; Abdallah, Alaa E.; Bsoul, Mohammad; Awwad, Sari
Abstract: We present a robust and unnoticeable secure image watermarking approach using Nonnegative Matrix Factorization (NMF) and Fast Walsh-Hadamard Transform (FWHT). The core idea of the proposed scheme consist of four key steps: The original cover image is divided into small blocks. The NMF is then applied to each block separately, followed by using the FWHT to the generated weight matrix. Finally, the singular values of the watermark image are distributed over the transformed blocks. The experimental results certainly show enhanced visual imperceptibility and exceptional resiliency against various types of attacks.